Stagnation point hybrid nanofluid flow past a stretching/shrinking sheet driven by Arrhenius kinetics and radiation effect - Nurul Amira, Zainal; Iskandar, Waini; Najiyah Safwa, Khashi’ie; Abdul Rahman, Mohd Kasim; Naganthran, Kohilavani; Roslinda, Nazar; Pop, Ioan (Elsevier B.V., 2023)
The exclusive behaviour of hybrid nanofluid has been actively emphasized due to the determination of improved thermal efficiency. Therefore, the aim of this study is to highlight the stagnation point Al2O3-Cu/H2O hybrid nanofluid flow with the influence of Arrhenius kinetics and thermal radiation over a stretching/shrinking sheet. This particular work is distinctive because it presents a novel hybrid nanofluid mathematical model that takes into account the highlighted issue with a combination of multiple consequences that have not yet been addressed in prior literature. The bvp4c package embedded in MATLAB software is used to address the formulated ordinary differential equations and specified boundary conditions based on similarity solutions. The flow is assumed to be incompressible and laminar, and the hybrid nanofluid is made up of two different types of nanoparticles. The findings demonstrate the viability of dual solutions within the defined ranges of the physical parameters. As predicted, the hybrid nanofluid flow has been convincingly proved to enhance the skin friction coefficient and the heat transfer performance as opposed to viscous flow and nanofluid flow. The heat of reaction and radiation parameters also act as contributing factors in the progress of thermal enhancement. On the other hand, the reaction